IMMUNOLOGICAL CHARACTERISTICS OF PATIENTS WITH DIFFERENT CORNEAL DISORDERS TREATED BY LAMELLAR KERATOPLASTY BY MEANS OF A LLOPLANT BIOMATERIAL - R. Z. Kadyrov (SPb RAACI, 2014)
Abstract. We have performed immunological studies in forty-five patients who underwent lamellar keratoplasty by means of Alloplant biomaterial. Serum antibodies to eye tissue-specific antigens (bovine corneal protein (BCP)-54, lens alpha-crystallin, S-antigen) were tested, and IgG, A, M in the lacrimal fluid were also determined, to detect cellular sensitization against same antigens, and to evaluate the levels of local non-specific inflammation. Percentage of cells activated for BCP-54 was found to be significantly decreased after surgery (p < 0.04), followed by increase to initial levels (p > 0.20) at later terms. Percentage of cells activated for lens α-crystallin was shown to be decreased upon further observation (p < 0.04). A post-surgical increase in IgG levels was revealed in lacrimal fluid (p < 0.02), followed by a decrease later on (p < 0.002). Thus, application of Alloplant biomaterial for lamellar keratoplasty does not cause any sufficient tension of specific humoral immunity against ocular tissues, as evidenced by lack of statistically significant changes of humoral and cellular immunity during post-surgical observations.